PENGARUH JAM KERJA TERHADAP KEBERHASILAN ASI EKSKLUSIF DI PUSKESMAS KEDUNDUNG MOJOKERTO - MAIL, ERFIANI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Exclusive breastfeeding is the infant only breast-fed only, without the addition of other liquids, such as formula milk, orange juice, honey, tea, water and without the addition of solid foods such as banana, papaya, milk porridge, biscuits, rice gruel and teams. Data coverage of exclusive breastfeeding in the PHC kedundung in 2013 as much as 12.5%, in 2014 as much as 37.3%, in 2015 as much as 54.6%. The purpose of this study was to analyze the effect of the work towards the success of exclusive breastfeeding in the PHC kedundung Mojokerto. Analytic observational research with case control design with a sample of cases and controls by 70 mothers of infants. Data were analyzed using univariate, bivariate and multivariate analysis with logistic regression. The results of this study indicate that the work hours of work ? 8 hours is significant to the success of exclusive breastfeeding (OR = 4.374; 95% CI: 1.409 to 13.576). Conclusion: ? 8 hours work hours have an effect on the success of exclusive breastfeeding. Suggestions can be drawn based on the results of this research are health education should be given to working mothers about the importance of exclusive breastfeeding. Keywords: exclusive breastfeeding, mothers, working